Real-world healthcare resource utilization related to migraine treatment failure: a panel-based chart review in France, Germany, Italy, and Spain. (2nd September 2019) - Vo, Pamela; Gao, Wei; Zichlin, Miriam L.; Fuqua, Eleanore; Fadli, Ela; Aguirre Vazquez, Marta; Tarancón, Thaïs; Mahieu, Nicolas; Maier-Peuschel, Monika; Rossi, Silvia; Naclerio, Mariantonietta; Ritrovato, Daniela; et al.
Abstract: Aims: This retrospective chart review examined the six-month migraine-related healthcare resource use (HRU) among European patients who had ≥4 migraine days per month and previously failed at least two prophylactic migraine treatments. Methods: Neurologists, headache specialists, and pain specialists in France, Germany, Italy, and Spain who treated ≥10 patients with migraine in 2017 were recruited (April–June 2018) to extract anonymized patient-level data. Eligible physicians randomly selected charts of up to five adult patients with clinically-confirmed migraine, ≥4 migraine days in the month prior to the index date, and had previously failed at least two prophylactic migraine treatments. Treatment failure was defined as discontinuation due to lack of efficacy and/or tolerability. Demographic and disease characteristics as of the index date, and migraine-related HRU incurred during the 6-month study period, were recorded. Results: A total of 104 physicians contributed 168 charts for patients (63% female). On average, patients were 38 years old and failed 2.3 prophylactic treatments as of the index date. During the study period, 83% of patients had ≥1 outpatient visit for migraine in the physician's office, and 27% went to the ER/A&E. Approximately 5% of patients were hospitalized for migraine, with an average of one hospitalization and an average length of stay of 3 days. Approximately 39% of patients had ≥1 blood test, 22% had ≥1 magnetic resonance imaging, 17% had ≥1 electroencephalogram, and 13% had ≥1 computerized tomography scan. Visits to other healthcare providers were common. Limitations: This study is subject to the limitations of chart review studies, such as errors in data entry. Conclusions: Across four European countries, the HRU burden of migraine among patients who previously failed at least two prophylactic treatments was high, indicating a need for more effective prophylactic treatments to appropriately manage migraine and reduce the HRU burden attributable to this common disorder.